PELESTARIAN RANDAI OLEH SANGGAR SALUAK BADETA DAN GENERASI MUDA SINTUAK TOBOH GADANG - Putri, Clara; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to analyze the Randai art preservation strategy by Sanggar Saluak Badeta and the involvement of the younger generation in Nagari Sintuak Toboh Gadang in facing the challenges of modernization. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation, which were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study revealed that Sanggar Saluak Badeta plays a central role in maintaining the existence of Randai through regular training programs, performances in traditional ceremonies, and intensive coaching for the younger generation who now play an active role as artists and organizational activists. The preservation strategy implemented includes adaptive performance innovation without reducing the value of originality, cross-sectoral collaboration with cultural institutions, and optimization of digital technology for documentation and promotion. It is concluded that the success of Randai preservation in this region is the result of collective synergy between art institutions, the active participation of the younger generation, and the support of the local community who have a high awareness of the sustainability of Minangkabau cultural heritage.